Exploring the Role of Bond Markets in Economic Growth: Evidence from a Split-Sample Analysis of EU Countries - Puscasu, Ela-Andrada (Technium Social Sciences Journal, 2025)
This paper investigates the relationship between bond market development and economic growth across 27 European Union countries over the period 2005–2021. While financial development has traditionally focused on banking and equity markets, the role of bond markets in supporting long-term growth remains underexplored, particularly in the heterogeneous European context. Using panel regression techniques, pooled OLS, fixed effects, and random effects, this study examines how key indicators such as bond yields and corporate bond issuance influence GDP growth and GDP per capita growth. The analysis is further refined through a split-sample approach, distinguishing between above-average and below-average GDP economies to assess the role of financial maturity. Results show that bond yields consistently exhibit a negative relationship with growth across all models, with a stronger effect in lower-GDP countries, underscoring their vulnerability to borrowing costs. Surprisingly, corporate bond issuance is negatively associated with growth, suggesting inefficiencies or debt misallocation in both advanced and developing markets. Meanwhile, stock market capitalization remains a robust and positive driver of growth, particularly in more mature economies. The findings highlight the asymmetric performance of bond markets and emphasize the need for differentiated financial development policies across EU member states. These insights have critical implications for capital market integration efforts and call for more targeted strategies aligned with national financial structures.